Coordination chemistry of the PdmBOX pincer ligand: reactivity at the metal and the ligand - Wenz, Jan; Vasilenko, Vladislav; Wadepohl, Hubert; Gade, Lutz H. (European journal of inorganic chemistry, 2017)
The coordination chemistry of PdmBOX [2,5-bis(2-oxazolinyldimethylmethyl)pyrrole] pincer ligands, in which a dimethylmethylidene linker has been introduced to preclude rearrangements in the backbone, has been studied with 3d and 4d late transition metals. The in situ lithiated PdmBOX ligand was treated with MnCl2, FeCl2 and CoCl2 to give [iPr(PdmBOX)MCl] (M = Mn: 2; Fe: 3; Co: 4) which were found to adopt a distorted tetrahedral coordination geometry in the crystal. Addition of 2,6-dimethylphenylisocyanide to 3 gave the diamagnetic tris(isocyanide) derivative [iPr(PdmBOX)Fe(CNxyl)3]Cl (5) with the chloride as the counteranion. Complexes 2-4 were found to be precatalysts for the enantioselective hydrosilylation and hydroboration of acetophenone. The synthesis of PdmBOX-palladium(II) complexes was achieved by deprotonation of the protioligand with potassium bis(trimethylsilyl)amide (KHMDS) and subsequent reaction with [(cod)PdCl2] giving [iPr(PdmBOX)PdCl] (6) or by stirring (S)-iPr(PdmBOX)H with palladium acetate yielding the palladium acetato complex 7. Treatment of the latter with phenylsilane at 60 °C also led to the slow formation of the metal hydride complex which was the key species in the catalytic hydrosilylation of styrene oxide, albeit with low activity. The coordination of (S)-iPr(PdmBOX)H to rhodium(I) was accomplished by reaction with (acetylacetonato)dicarbonylrhodium(I) to give the corresponding PdmBOX-Rh complex 8 which reacted with methyl iodide to give the octahedrally coordinated rhodium(III) complex [iPr(PdmBOX)Rh(CH3)I(CO)] 9. Reaction of 8 with one equivalent of CsBr3 led to the full conversion to the dibromorhodium(III) complex [iPr(PdmBOX)Rh(CO)Br2] 10. Upon reaction of 10 with N-bromosuccinimide (NBS), the pyrrole backbone in 10 was brominated to give complex 11. In a similar way, a selective conversion of [iPr(PdmBOX)NiCl] to the backbone-chlorinated [iPr(ClPdmBOX)NiCl] (12) was achieved by the treatment with N-chlorosuccinimide.